Designing business architecture for machinery distribution company using the open group architecture framework method - Ananda, Vincent Ray; Lee, Francka Sakti; Breliastiti, Ririn (Institute of Advanced Engineering and Science, 2025)
Machinery distribution company plays a crucial role in supporting various industries by providing the necessary machines and spare parts. This research focuses on the challenges faced by machine distribution companies in Jakarta, which have branches in Surabaya and Medan, Indonesia, especially in the management of warehouse data. The manual inspection process of stored goods for a long period of time results in operational inefficiencies and increased costs. To address this issue, this research proposes the application of enterprise architecture, specifically business architecture, using the open group architecture framework (TOGAF). This method to design optimal business processes that can improve productivity, reduce human errors, and enhance service quality. Through the analysis of current business processes and the planning of enterprise model interactions, this research identifies gaps in business architecture and designs business architecture to support the company's goals. The research results are expected to help companies improve operational efficiency and competitiveness in a constantly changing market.